2009
DOI: 10.1038/sc.2008.172
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcome of sacral neuromodulation in incomplete spinal cord injured patients suffering from neurogenic lower urinary tract symptoms

Abstract: Objective: To determine the efficacy and safety of sacral neuromodulation (SNM) in incomplete spinal cord injured (SCI) subjects affected by neurogenic lower urinary tract symptoms (NLUTS). Methods: Twenty-four SCI patients were enrolled. The individuals were divided into two groups: 13 individuals in the urinary retention category and 11 suffering from overactive bladder syndrome. All subjects underwent definitive SNM implantation (Medtronic, Inc.). Voiding symptoms were assessed using patient bladder diaries… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
38
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 73 publications
(40 citation statements)
references
References 20 publications
1
38
0
1
Order By: Relevance
“…1 Recently it has been shown that incomplete spinal cord injury patients (SCIPs) make remarkable clinical improvements with sacral neuromodulation (SNM), either in neurogenic bowel symptoms (NBSs) or in neurogenic lower urinary tract symptoms (NLUTSs). 2,3 Moreover, literature reports SNM's positive clinical effects on erectile function in SCIP as well. 4 The aim of this study was to conduct medium and long follow-ups of SNM efficacy in SCIPs who had shown significant clinical improvement in more than one pelvic functional disturbance with a permanent SNM implant.…”
Section: Introductionmentioning
confidence: 99%
“…1 Recently it has been shown that incomplete spinal cord injury patients (SCIPs) make remarkable clinical improvements with sacral neuromodulation (SNM), either in neurogenic bowel symptoms (NBSs) or in neurogenic lower urinary tract symptoms (NLUTSs). 2,3 Moreover, literature reports SNM's positive clinical effects on erectile function in SCIP as well. 4 The aim of this study was to conduct medium and long follow-ups of SNM efficacy in SCIPs who had shown significant clinical improvement in more than one pelvic functional disturbance with a permanent SNM implant.…”
Section: Introductionmentioning
confidence: 99%
“…Our findings are in concordance with other studies reporting a loss of SNM efficacy in four patients in whom a worsening of the neurological status and technical problems could be ruled out. 17 Loss of SNM function seems to occur even more frequently in MS patients. Chaabane et al demonstrated a loss of SNM effect in 41% of the MS patients, most often because of progressive neurological disease.…”
Section: Discussionmentioning
confidence: 99%
“…In the patients with NDO combined with DSD, neither objective nor subjective SNM success was observed, whereas in patients with pure NDO, a significant decrease in incontinence and in urodynamic parameters could be observed. 17 Chaabane et al 18 presented a retrospective case series with 62 patients suffering from NLUTD: the majority from multiple sclerosis (MS) or incomplete SCI (13 patients each) and the remaining patients from various neurologic disorders. In their study, SNM led to a significant improvement not only of symptoms but also of urodynamic parameters including improvement of DSD in eight of nine patients.…”
Section: Discussionmentioning
confidence: 99%
“…3,17,18 However, the repetitive use of endoscopic detrusor injections of low dosages of BoNT-A never required the use of AIC to increase the post-voiding residual urine ml -1 on the two patients who did not respond to first stage of SNM. In one patient, recurrence was observed after about 4 years.…”
Section: Discussionmentioning
confidence: 99%